An assessment of mental health programs at community health centers in north Minahasa, Indonesia - Mogi, Jessica Gloria; Ratag, Gustaaf A. E. (International Journal Of Community Medicine And Public Health, 2021)
Background: The Indonesian government recognizes the importance of mental health issues as indicated by the inclusion of such issues as indicators in the national program, the Healthy Indonesian Program with Family Approach (PIS-PK). This program is enforced in community health centers (puskesmas) in every regency in the country. However, the continually increasing number of mental disorder cases and the intense stigmatization of people with these disorders indicate the need to re-evaluate the capacity and delivery of designated centers’ mental health programs. Methods: This community survey involved interviewing the program directors of four community health centers in north Minahasa using the WHO-AIMS 2.2 questionnaire. Results: Very little effort has been made to improve mental health facilities and programs. Examples of aspects of health facilities that are lacking include training for health workers, the provision of psychotropic drugs, and supported employment or occupational rehabilitation. Conclusions: Community health centers are primary healthcare facilities for society. Therefore, mental health services should be implemented as one of their main programs.